Prophetically incorrect : a Christian introduction to media criticism - Woods, Robert, 1970-; Patton, Paul, 1952- (Grand Rapids, Mich. : Brazos, 2010)
Using vivid examples, this book offers clear guidelines for creating, critiquing, and consuming popular media, as well as practical suggestions for faithful communication. It also helps readers think critically about communication technology. --from publisher description
Communicating faithfully in a culture of ideological division -- Cultivating a prophetic voice -- Becoming burdened -- Considering humanity's plight -- Rejecting a spirit of acceptance -- Shocking the complacent -- Promoting prophetic critique of technology: a case study -- Conclusion: considering the downs and ups of prophetic media criticism.
Includes bibliographical references (p. 131-171) and index.
Keywords: Mass media -- Religious aspects -- Christianity; Christianity and culture